2018
DOI: 10.1007/s00330-018-5616-7
|View full text |Cite
|
Sign up to set email alerts
|

Does gadoxetate disodium affect MRE measurements in the delayed hepatobiliary phase?

Abstract: Objectives To assess if the administration of gadoxetate disodium (Gd-EOB-DTPA) significantly affects hepatic magnetic resonance elastography (MRE) measurements in the delayed hepatobiliary phase (DHBP). Methods A total of 47 patients (15 females, 32 males; age range 23-78 years, mean 54.28 years) were assigned to standard hepatic magnetic resonance imaging (MRI) with application of Gd-EOB-DTPA and hepatic MRE. MRE was performed before injection of Gd-EOB-DTPA and after 40-50 min in the DHBP. Liver stiffness v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is important in this step that the radiographer is well trained to guide the patients through the breathing cycle and also that the radiographer checks the respiratory patients' movement from the internal camera before the start of the acquisition. In our experience, we did not perform MRE after the administration of contrast medium, as different study results have shown no significant differences in stiffness values when performing MRE before and after contrast medium administration [5,33].…”
Section: Acquiring the Imagesmentioning
confidence: 93%
“…It is important in this step that the radiographer is well trained to guide the patients through the breathing cycle and also that the radiographer checks the respiratory patients' movement from the internal camera before the start of the acquisition. In our experience, we did not perform MRE after the administration of contrast medium, as different study results have shown no significant differences in stiffness values when performing MRE before and after contrast medium administration [5,33].…”
Section: Acquiring the Imagesmentioning
confidence: 93%
“…Finally, MRE scanning was conducted before contrast enhancement in our study. According to prior researches, 27,28 contrast administration did not significantly influence MRE stiffness measurements of liver, but its potential influence for tumor assessment has not been well understood, and might be an interesting avenue for future work. Furthermore, the application of threedimensional MRE, especially in smaller lesions, needs to be investigated.…”
Section: Limitationsmentioning
confidence: 95%
“…Study results (42,43) have shown that the administration of gadolinium-based contrast material has no effect on liver stiffness, and thus there is no substantial difference between the liver stiffness measured before and that measured after intravenous injection of a gadolinium-based contrast agent. Finally, the liver fat and iron quantification usually performed with MR elastography still should be performed before contrast agent administration to avoid the effects of gadolinium on these measurements (Fig 6).…”
Section: Pulse Sequence Timingmentioning
confidence: 98%